Can University/Community Collaboration Create Spaces for Aboriginal Reconciliation? Case Study of the Healing of the Seven Generations and Four Directions Community Projects and Wilfrid Laurier University - Lafrenière, Ginette; Diallo, Papa Lamine; Dubie, Donna; Henry, Lou (First Peoples Child & Family Review, 2005)
In this article, the authors attempt to illustrate how two Aboriginal community-based projects were conceptualized and developed through the collaborative efforts of four individuals who believed in the merits of a project aimed at survivors and intergenerational survivors of the residential school system as well as Aboriginal people in trouble with the law. Drawing upon a small body of literature on university/community collaboration, the authors illustrate the importance of meaningful collaboration between universities and communities in order to enhance a mutually beneficial relationship conducive to community-engaged scholarship. Through an examination of the case study of the Healing of The Seven Generations Project and the Four Directions Aboriginal Restorative Justice Project, the authors hope to illustrate to fellow Aboriginal colleagues in Canada the merits, strengths and challenges of university/ community collaboration. Ultimately, what the authors hope to share through this article is an example of how university/community collaboration can create spaces whereby Aboriginal people have become agents of their own healing.